A Novel Mutation in the AVPR2 Gene in a Palestinian Family with Nephrogenic Diabetes Insipidus - Abu-Libdeh, Abdulsalam; Wexler, Isaiah D.; Dweikat, Imad; Zangen, David; Abu-Libdeh, Bassam (Journal of Child Science, 2017)
Nephrogenic diabetes insipidus (NDI) is a urinary concentrating defect resulting from resistance of the collecting duct to the antidiuretic action of vasopressin (AVP). The X-linked recessive form is the most frequent genetic cause of inherited NDI and can be caused by mutations in the gene encoding the V2 vasopressin receptor (AVPR2). A Palestinian male infant presented in the neonatal period with failure to thrive, vomiting, irritability, fever, and polyuria, and had biochemical findings consistent with NDI. The diagnosis of NDI was established based on the clinical picture, absent response to desmopressin, and a similarly affected elder brother. Sequencing of the AVPR2 gene for the patient and his affected brother revealed a novel missense mutation with replacement of G by A in codon 82 located in exon 2 (TGC → TAC), causing a cysteine to tyrosine substitution (C82Y). Testing of the mother showed that she was the carrier of that mutation. This is the identified AVPR2 mutation in a Palestinian family. Knowledge of these mutations will allow genetic counseling and early diagnosis of affected males.
Keywords: nephrogenic diabetes insipidus; AVPR2; hypernatremia; vasopressin; vasopressin receptor